PENGEMBANGAN MODUL AJAR KURIKULUM MERDEKA BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Nilma Aprianti; Muhammad Arsyad; Pariabti Palloan (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
This study is Research and Development (R&D). Development was conducted by referring to the ADDIE model. The ADDIE stages included the analysis, design, development, implementation, and evaluation stages. This development research aims to: (1) produce independent curriculum teaching modules based on local wisdom to improve students' critical thinking skills that meet valid criteria, (2) produce independent curriculum teaching modules based on local wisdom to improve students' critical thinking skills that meet practical criteria, (3) describe the effectiveness of using independent curriculum teaching modules based on local wisdom to improve the developed critical thinking skills of students. The test subjects for this research were 35 students in grade X.B of SMAN Negeri 12 Luwu. The instruments used in this research were validation sheets for teaching modules based on local wisdom, practitioner assessment questionnaires, namely Physics subject teachers, and critical thinking skills test instruments. The eligibility criteria for teaching modules were based on the content validity aspect. The criteria for the practicality of the Physics teaching modules were based on the assessment of practitioners (Physics teachers), and the criteria for the effectiveness of using local wisdom-based teaching modules were based on the increase in students' critical thinking skills test results. Based on the results of the analysis, the conclusions obtained are: (1) the validity of the independent curriculum teaching modules based on local wisdom which had been developed, based on the results of the Aiken's V content validity coefficient has met the valid/feasible category; (2) the practitioners' responses to the independent curriculum teaching modules based on local wisdom which had been developed, gave positive responses in very good category; (3) the effectiveness of using independent curriculum teaching modules based on local wisdom with a percentage of 57% is in effective category. This means that the local wisdom-based teaching module that had been developed is effective in improving students' critical thinking skills.